Pe Manfaat Lidah Buaya Sebagai Bahan Baku Pembuatan Body Lotion - Lativa, Lativa Laura; Murazakia, Ana; Reflianto (Jurnal Tata Rias, 2025)
Aloe vera is a medicinal plant rich in nutrients and active compounds such as vitamins, enzymes, and antioxidants that benefit skin health. In the cosmetic industry, aloe vera is widely used as a natural ingredient in body lotion formulations due to its moisturizing, soothing, and skin-regenerating properties. This article discusses the benefits of aloe vera as a primary raw material in the production of body lotion, including its ability to hydrate the skin, reduce irritation, and delay signs of aging. Aloe vera-based body lotions are also considered safe and suitable for various skin types, including sensitive skin. With its natural content, aloe vera has great potential as a sustainable and eco-friendly base ingredient for personal care products.